2015
DOI: 10.1093/gji/ggv270
|View full text |Cite
|
Sign up to set email alerts
|

3-D analysis and interpretation of magnetotelluric data from the Aluto-Langano geothermal field, Ethiopia

Abstract: The Main Ethiopian Rift Valley encompasses a number of volcanoes, which are known to be actively deforming with reoccurring periods of uplift and setting. One of the regions where temporal changes take place is the Aluto volcanic complex. It hosts a productive geothermal field and the only currently operating geothermal power plant of Ethiopia. We carried out magnetotelluric (MT) measurements in early 2012 in order to identify the source of unrest. Broad-band MT data (0.001-1000 s) have been acquired at 46 sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 59 publications
7
100
1
Order By: Relevance
“…Additionally, there is a systematic mismatch in the phase values for both the stations directly above and further to the east of the conductor, which are better reproduced in the preferred inversion model. This confirms that the presence of a deeper conductor is required to explain data from the western‐central section of the profile and is in accordance with the forward modeling of tipper data on Aluto by Samrock et al (). We also tested the sensitivity of the MT data to a conductive feature representing a shallow magma chamber under Aluto and found that the presence of such a feature would easily be detected by the data collected above it (see supporting information Figure S3).…”
Section: Model Assessment and Robustness Of Featuressupporting
confidence: 90%
See 3 more Smart Citations
“…Additionally, there is a systematic mismatch in the phase values for both the stations directly above and further to the east of the conductor, which are better reproduced in the preferred inversion model. This confirms that the presence of a deeper conductor is required to explain data from the western‐central section of the profile and is in accordance with the forward modeling of tipper data on Aluto by Samrock et al (). We also tested the sensitivity of the MT data to a conductive feature representing a shallow magma chamber under Aluto and found that the presence of such a feature would easily be detected by the data collected above it (see supporting information Figure S3).…”
Section: Model Assessment and Robustness Of Featuressupporting
confidence: 90%
“…Below, a resistive layer extends to about 15 km depth. Under Aluto, the subsurface is resistive at depths < 3 km, which confirms the results from the much higher‐resolution 3‐D model from Samrock et al (), but which was based on a smaller array aperture ‐ and hence limited depth resolution ‐ of MT stations around the volcano edifice. With the frequency content of our data and the profile length in this study, we would have identified a deeper conductive anomaly under or around Aluto that might be expected from significant amounts of magma or partial melt, known to be present from geodesy, seismology, and degassing studies, had it existed.…”
Section: The Electrical Resistivity Model Along the Transectsupporting
confidence: 82%
See 2 more Smart Citations
“…1). One example is the Aluto-Langano geothermal system in the central part of the Main Ethiopian Rift (MER), where InSar (Interferometric Synthetic Aperture Radar) analysis has identified ongoing surface deformation with cycles of uplift and subsidence (Biggs et al, 2011), and which hosts a welldeveloped hydrothermal reservoir and a productive geothermal field (Gizaw, 1993;Teklemarian et al, 1996;Samrock et al, 2015). Besides Aluto, knowledge of the geothermal potential of other areas in Ethiopia has increased in recent years; examples include i) Tendaho in the Afar depression (Didana et al, 2015), ii) Gedemsa-Sodere and iii) Corbetti (Teklemarian and Kebede, 2010;Kebede, 2014); these latter two are located within the MER.…”
Section: Introductionmentioning
confidence: 99%